Engage Green Customer Loyality on Green Hotel Services : Mediating Role of Satisfaction Case in Yogyakarta - Nining Yuniati (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
Green customers are not typical consumers in general, but they have specific characteristics and motivations related to their decisions to use environmentally friendly products. Green customers are also known as a loyal and fanatical market group. One example is the decision regarding the use of eco-friendly accommodation or green hotels. Some eco-friendly products, including green hotels, are often claimed to be uncomfortable but have premium rates. However, the fact is that green hotels are still highly appreciated by their users. This research is an examination of the green customer loyalty model in a green hotel accommodation in Yogyakarta. The proposed propositions are whether green customers are truly loyal and whether customer satisfaction plays a role in increasing the loyalty of green customers. This model was tested on 153 guests randomly. The testing was conducted using construct validity and reliability tests with SEM-PLS analysis. The results showed that green customers will become loyal customers through the mediation of green hotel services that can meet their expectations, such as eco-friendly attributes, the atmosphere, the unique design of the hotel, energy efficiency, the hotel's initiative to encourage customer involvement in green actions, employee attitude and awareness, healthy food, and special rewards for bio menu.